Comparative Analysis of Biochar Properties from Lemon and Kumquat Peels at Different Pyrolysis Temperatures - Limmun, Wanida; Limmun, Warunee; Ito, Ayumi; Choolaaied, Orasa; Phanchindawan, Naree; Chungcharoen, Thatchapol (My University, 2025)
This study examines the effects of pyrolysis temperatures (500 °C and 700 °C) on the properties of biochar derived from lemon peel (LB), kumquat peel (KB), and their combination (LKB). The study analyzed the variations in biochar yield, elemental composition, and specific surface area. The results indicated that higher temperatures led to a reduction in yield but a significant improvement in specific surface area, pore volume, and carbonization, ultimately producing more stable and aromatic biochar. Additionally, LB700 and KB700 exhibited more developed pore structures and higher specific surface areas than those produced at 500 °C. Elemental analysis showed an increase in carbon content and a decrease in hydrogen content at elevated temperatures, suggesting improved biochar stability. These findings demonstrate that higher pyrolysis temperatures enhance the specific surface area and carbon content of biochar, making it more suitable for environmental applications such as soil quality improvement and pollutant adsorption. The study highlights the potential of using commonly discarded agricultural waste, such as lemon and kumquat peels, for biochar production.
Keywords: Biochar; Kumquat peel; Lime peel; Pyrolysis temperature